Sustainable Urbanization - Ergen, Mustafa (IntechOpen, 2016)
The rapid urbanization that began with industrialization has begun to cause many problems. New approaches are emerging today to minimize these problems and make urban areas more livable. These problems include insufficient social facilities in urban areas for increasing populations due to migration and unbalanced use of green areas, water, and energy resources due to urbanization. Careless consumption and the pollution of natural resources will cause people many more problems in the future than they do today in urban development. Many professional disciplines have noticed this unbalanced development in urban areas. Urban areas have larger populations than rural areas today. Urban areas are developed neglectfully. Sustainability is needed as a criterion for urban areas to develop in a more livable and healthy fashion. Sustainable urban development approaches are seen in many fields, ranging from land use to the use of natural resources in urban areas.